How Silence Contributes to the Performance of Sincerity in Psychotherapy - Israel Berger; John P. Rae (Psychotherapy and Counselling Journal of Australia)
Most literature concerning silence in psychotherapy has focused on the meaning of silences, particularly from psychoanalytic perspectives, and is based on clinical experience rather than empirical studies. These authors tend to interpret silence as pathology or resistance in the client and/or advise clinicians to be especially tolerant of silence and to avoid filling silences. Although some studies have found that moderate silence is correlated with better outcomes, these studies ignore psychosocial aspects of the interaction. No research has looked at silence in psychotherapy as a linguistic device to manage the local sequential environment. Silence following an initiating action is characteristic of dispreferred responses such as refusals and negatively valenced answers in general conversation. In this study, we used conversation analysis to explore preference and the role of silence in nine spiritually oriented humanistic psychotherapy sessions. We found that in contrast to everyday conversation, in these interactions, there is a preference for gaps and pauses while immediate responses are dispreferred.